Spectroscopy: Gain Spectroscopy of Solution‐Based Semiconductor Nanocrystals in Tunable Optical Microcavities (Advanced Optical Materials 2/2016). Issue 2 (February 2016) - Patel, Robin K.; Trichet, Aurélien A. P.; Coles, David M.; Dolan, Philip R.; Fairclough, Simon M.; Leontiadou, Marina A.; Tsang, S. C. Edman; Binks, David J.; Jang, Eunjoo; Jang, Hyosook; Taylor, Robert A.; Smith, Jason M.
Abstract : J. M. Smith and co‐workers demonstrate a new design of miniature tunable dye laser using solution‐based colloidal CdSe/CdS core/shell quantum dots in open access optical microcavities. On page 285, these devices provide a new method to probe the optical gain properties of quantum dots by tuning the cavity mode through the emission band and measuring the changing lasing threshold. The size of the microcavities and the ability to manufacture arrays makes the laser devices suitable for on‐chip integration.